Effect of ammonium/phosphate molar ratio on struvite production via electrolysis using a sacrificial magnesium anode - Pangestu, Aditya Kurnia Aji; Bagastyo, Arseto Yekti; Nurhayati, Ervin; Lin, Jr-Lin; Sidik, Fahrudin (Sustinere: Journal of Environment and Sustainability, 2025)
Excessive ammonium and phosphate levels in aquatic environments potentially cause eutrophication, leading to water quality imbalance, algal blooming, and disturbance of biodiversity status. Electrolysis using a sacrificial magnesium anode effectively removes and recovers ammonium and phosphate, producing struvite (MgNH4PO4.6H2O). The present study investigated the optimum current density and the effect of the ammonium/phosphate molar ratio on struvite production. The current density was controlled at 10, 50, and 100 mA/cm2. An artificial wastewater containing [NH4+]:[PO43-] in a molar ratio of 1:10, 1:1, and 10:1 was used as the test solution. The optimum current density was determined as 50 mA/cm2. The ammonium and phosphate reduction ratios at a 1:1 molar ratio was approximately 46.91% and 74.26%, respectively. Increasing the ammonium molarity in the test solution to 10:1 increased the phosphate reduction ratio to 96.38% while decreasing the ammonium reduction ratio to 26.28%. The maximum precipitation of 4.1914 g was generated at a molar ratio of 10:1 with a specific energy consumption of 0.011 Wh/mg-P, out of the three ammonium/phosphate molar ratio variations. Microscopes and SEM-EDS were used to characterize the precipitates produced, and Visual MINTEQ 3.1 was then used for modeling.